2005
DOI: 10.1375/brim.2005.6.3.212
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Time of Day Effects on Mini-Mental State Examination Performance in Alzheimer's Disease and Age-Associated Cognitive Decline

Abstract: N europsychological assessment plays a prominent role in the diagnosis of Alzheimer's disease (AD) and other cognitive impairments. Increasingly, neuropsychological test results are also used to guide clinicians in the prescription of anti-dementia medication. There is evidence to suggest that the cognitive ability of an individual with AD may vary over the course of a day. If time of day can influence an individual's performance on cognitive tests, then it could potentially affect his or her diagnosis and eli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 27 publications
0
4
1
Order By: Relevance
“…Time of day may be a factor in the performance of visual copying in persons with AD. 18,24 Our results did not support any changes in cognitive functioning based on TOD as tested. We tested in the AM (9:30-11:30) and PM (2:30-4:30).…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…Time of day may be a factor in the performance of visual copying in persons with AD. 18,24 Our results did not support any changes in cognitive functioning based on TOD as tested. We tested in the AM (9:30-11:30) and PM (2:30-4:30).…”
Section: Discussioncontrasting
confidence: 80%
“…Published studies on the effect of TOD on cognitive efficiency in patients with Alzheimer's dementia are very limited and results are conflicting. 18,20 In a study measuring crystallized and fluid abilities in healthy adults ranging in age from 20 to 78 (mean age 44.77 years), Brown et al found that age was a significant predictor for 2 of the tasks whereas TOD did not predict performance for any of the 3 types of tasks (vocabulary, verbal fluency, and trail making test). They concluded that TOD influences may be limited to specific types of cognitive abilities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This reduced sensitivity to synchrony for neutral-type individuals may account for some of the discrepant findings regarding the influence of synchrony on cognitive performance, as a number of studies demonstrating small or absent synchrony effects have either intentionally included neutral-type individuals in their sample or failed to assess chronotype altogether (e.g., Barbosa & Albuquerque, 2008; Breslin, 2019; Brown et al, 2005; Bugg et al, 2006; Knight & Mather, 2013; B. Martin et al, 2008; Roeser et al, 2015; Root Kustritz et al, 2022; Rothen & Meier, 2017; Tandoc et al, 2021).…”
Section: Limits To the Synchrony Effectmentioning
confidence: 99%
“…This reduced sensitivity to synchrony for neutral-type individuals may account for some of the discrepant findings regarding the influence of synchrony on cognitive performance, as a number of studies demonstrating small or absent synchrony effects have either intentionally included neutral-type individuals in their sample or failed to assess chronotype altogether (e.g., Barbosa & Albuquerque, 2008;Breslin, 2019;Brown et al, 2005;Bugg et al, 2006;Knight & Mather, 2013;Martin et al, 2008;Roeser et al, 2015;Root Kustritz, Bakke, & Rendahl, 2022;Rothen & Meier, 2017;Tandoc et al, 2021). Given that up to 50% of young adults and 25% of older adults do not show strong morning or evening preferences, it is likely that samples drawn from the general population will include significant proportions of neutral-types, thus diluting the synchrony effects experienced by those with strong chronotypes.…”
Section: Limits To the Synchrony Effectmentioning
confidence: 99%